EVALUATING IN-SERVICE GIS TRAINING FOR GEOGRAPHY TEACHERS BASED ON G-TPACK MODEL - (:unkn) unknown (My University, 2021)
Many different barriers have been identified which limit integration of spatial technologies into secondary school education. Becauseof these challenges teachers tend to concentrate traditional teaching methods instead of removing obstacles on using spatialtechnologies. However, we may remove physical (lack of hardware, software) and technical (lack of computer) barriers in terms ofrequirements of geography teachers. Geography teachers who can combine their technological skills with pedagogical and fieldknowledge are the ones who meets today's educational needs. It is necessary to organize in-service training (IST) activities that canmeet today's needs in geography education, prepared in line with the needs of teachers and helpful in developing their technologicalcompetencies, to which they can participate voluntarily. The aim of this study was to develop, implement and evaluate in-servicetraining GIS course among geography teachers using an open source software, free data and geographical technological pedagogicalcontent knowledge (G-TPACK) model. The research employed both qualitative and quantitative research methods and techniques. Ourstudy proved that in-service GIS training which was admired to attend by teachers according to the needs analysis, have improvedtheir skills and knowledge.